2010
DOI: 10.1002/hep.23690
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid substitution in hepatitis C virus core region and genetic variation near the interleukin 28B gene predict viral response to telaprevir with peginterferon and ribavirin

Abstract: Genetic variation near the IL28B gene and substitution of amino acid (aa) 70 and 91 in the core region of hepatitis C virus (HCV) genotype 1b can predict the response to pegylated interferon (PEG-IFN)/ribavirin combination therapy, but its impact on triple therapy of telaprevir/PEG-IFN/ribavirin is not clear. The aims of this study were to investigate the predictive factors of sustained virological response to a 12-week or 24-week regimen of triple therapy in 72 of 81 Japanese adults infected with HCV genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
204
6
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 238 publications
(231 citation statements)
references
References 38 publications
16
204
6
2
Order By: Relevance
“…In this study, the genotype frequencies observed of individuals of different ethnicities uninfected with HCV are consistent with those of previous studies 14,15 specifically investigating the IL28B SNPs and SVR in HCV-infected patients.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the genotype frequencies observed of individuals of different ethnicities uninfected with HCV are consistent with those of previous studies 14,15 specifically investigating the IL28B SNPs and SVR in HCV-infected patients.…”
Section: Discussionsupporting
confidence: 91%
“…The significance of core 70 substitution has since been confirmed in large-scale studies [47,48]. No substitution at core 70 (70R) was found to be an independent predictive factor for SVR in a large-scale Japanese study into HCV G1b, treated by PEG-IFN plus RBV [49].…”
Section: Substitutions In Regions Other Than Ns5a In Association Withmentioning
confidence: 95%
“…According to the study of Akuta et al [51] genetic variations near the IL28B gene and aa substitutions in the core region were identified as predictors of viral dynamics during triple therapy.…”
Section: Substitutions In Regions Other Than Ns5a In Association Withmentioning
confidence: 99%
“…Data from these studies showed that the SVR rates of TVR-based triple therapy for 12 weeks were only 45% in treatment-naïve patients. 107,108 The SVR rates increased to 70%-82% with an additional 12 weeks of PEG-IFN α plus RBV, except for one small trial 112 enrolling the most difficult-to-treat partial responders and nonresponders, which showed an SVR rate of 27%. 107,[109][110][111][112][113][114][115] In line with Western reports, IL-28B genotypes and RVR strongly affected the SVR rates in Asian HCV-1 patients receiving BOC-or TVR-based triple therapy.…”
Section: Boc or Tvr-based Triple Therapy In Asian Patients With Chronmentioning
confidence: 99%